Building informal knowledge‐sharing relationships between policy makers and academics: Insights from a PM&C engagement project. Issue 2 (20th February 2019) - Quayle, Annette; Kelly, Bernadette
Abstract: This article outlines an innovative project to encourage knowledge sharing and engagement between academics and a policy team within the Department of the Prime Minister and Cabinet (PM&C). The project was designed to enhance policy advice by drawing on a group of academics outside the policy ranks to act as a sounding board, to question, and provide differing perspectives within the policy process of crafting advice to government. External expertise and particularly academic research has the potential to improve evidence‐based policy but often fails to be specific or timely for those at the "pointy end" of policy decision making. An informal knowledge sharing framework has the potential to improve the exchange of information through confidential and targeted conversations between researchers and public servants as one way of overcoming these barriers. Abstract : This article outlines an informal engagement framework between academics and policy advisors in the Department of the Prime Minister and Cabinet. The project drew together a group of academics outside the policy process to provide ad hoc, confidential, targeted, and timely advice as needed in real‐time policy decision making.